Investigating the antecedents of Potential Hypertension Patients’ Brand Loyalty and Brand Equity in Personal Health Assistant Services: A Case Study on a Private Hospital in Bangkok, Thailand - Charukitpipat, Artirat (Scholar: Human Sciences, 2024)
Purpose: The research has aim to investigate the antecedents of brand loyalty and brand equity in personal health assistant services perceived by patients with potential hypertension at a private hospital of Bangkok, Thailand. Research design, data and methodology: The research framework was conceptualized based on previous studies and theoretical frameworks, which consisted of perceived service quality, satisfaction, word-of-mouth, brand image, brand loyalty, and brand equity. The research has conducted the study with a group of 500 respondents with potential hypertension patients using purposive sampling, stratified random sampling, and convenience sampling. Questionnaires for data collection were verified for reliability of measurement items with Item-Objective Congruence (IOC) and pilot test. The collected data was then analyzed with Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: Brand image is an antecedent of both brand loyalty and brand equity, in which brand image was significantly impacted from word-of-mouth. Although perceived service quality impacted satisfaction, satisfaction has no significant relationship to brand loyalty. Conclusions: Brand marketers and service providers should focus on stimulating positive word-of-mouth and shaping brand image through service promotion and advertisement in order to create brand loyalty and brand equity in personal health assistance service.